Pengembangan Aplikasi Game Pengenalan Jenis-jenis Virus Berbasis RPG - Pradana, Dwifa Yuda; Vitianingsih, Anik Vega; Cahyono, Dwi; Wikaningrum, Anggit; Wati, Seftin Fitri Ana (Jurnal Teknologi Terpadu, 2024)
The global community has been significantly affected by the COVID-19 pandemic in terms of health, education, the economy, social matters, and culture. Digital devices are increasingly being used for entertainment to combat boredom amidst restrictions on physical activity. However, this behaviour can also reduce adherence to health protocols, which can lead to high cases of COVID-19. Education about viruses is increasingly emphasized, especially for adolescents, who are a key group in preventing the spread of viral infections. Consequently, the media is required to introduce the different kinds of viruses and their survival strategies. This study aims to create an RPG-based "V-Fight" game application for virus types' exposure among teens. The research used a software development methodology that applied the Multimedia Development Life Cycle (MDLC), which consists of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The validation test conducted on 35 respondents obtained a validity level of 76.38%. This indicates that the tested game has sufficient criteria to be considered a practical learning tool.